Does Exposure To Economics Bring New Majors To The Field? Evidence From A Natural Experiment - Andreas Steinmayr; Hans Fricke; Jeff Grogger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This study investigates how exposure to an academic field influences students major choices. In particular, we analyze whether students who are inclined to study business change their intentions after being exposed to economics or law. We exploit a natural experiment at a Swiss university. All first year students face the same curriculum before they chose a major. An important part of the curriculum is a first year paper in business, economics, or law. Due to oversubscription of business, the university assigns the field of the paper in a standardized way unrelated to student characteristics. We find that assignment to economics raises the probability of majoring in economics by 2.7 percentage points, which amounts to 18 percent of the share of students who major in economics. The effect is entirely driven by male students.
Keywords: I20; I23; A22; 330